The Value of Public Participation in Land-Use Planning for Redeeming Congestion in South African Municipalities - Kgobe, France Khutso Lavhelani; Mamokhere, John (Technium Social Sciences Journal, 2021)
This paper captures the value of public participation as a redeemer of South African municipalities in land use planning. In this paper, it is argued that there is scant public participation in local government developmental matters, especially in land-use planning. South African municipalities are congested due to lack of public participation in land-use planning in the municipal arena. This is despite the fact that the constitution requires active public engagement in questions of developing local administration. The challenge of inactive public participation endures throughout the IDP, and this is now perceived as a dream wish. It is further argued that it is important to involve the public in land-use, especially in the following categories: commercial, residential, public facilities, industrial, and open spaces. The arguments in this paper were also founded on Patsy Healey’s 1997 theory of collaborative planning. Collaborative planning theory has been used to develop ideas and arguments. This is a conceptual paper based on secondary data. The paper relied heavily on current literature on public participation and land-use planning. Despite the arrival of democracy in South Africa, the theoretical findings of this research indicated that there is still apartheid in spatial planning. It is also discovered that the adopted South African apartheid spatial planning continues to overlook community involvement in municipal land-use planning. When it comes to planning, the study proposes that municipal authorities follow the Batho Pele principles. At the municipal level, public engagement should not be passive but interactive and consultative. Finally, the paper advocates for land-use planning reforms and the use of active public engagement to save South African municipalities from congestion.